COMBINATION OF WP AND TOPSIS METHODS IN A DECISION SUPPORT SYSTEM FOR WATERMELON SEED RECOMMENDATION - Tejawati, Andi; Puspitasari, Novianti; Pasorong, Hillary Bella; Masa, Amin Padmo Azam (Jurnal Teknik Informatika (Jutif), 2024)
Watermelon is a horticultural plant that can be cultivated by the wider community with adequate profits. In Indonesia, watermelon production is still unable to meet the huge market demand and has not been able to be met by local watermelon-producing areas. One of the reasons why watermelon production is insufficient is because the fruit is easily damaged due to inappropriate watermelon seeds. The right watermelon seeds can be selected using a Decision Support System. This study uses two combination methods, namely Weighted Product (WP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), to be applied in the Decision Support System for watermelon seed recommendations. The WP method is used to determine the weight of the criteria, while TOPSIS is used to determine the order of watermelon seed recommendations. The data used in this study were twenty alternative watermelon seeds with five criteria, namely land recommendations, yield potential, fruit weight, harvest age, and disease resistance. Of the five criteria determined by the WP method, the largest criterion value is in the land recommendation. The results of the implementation with both methods produced recommendations for watermelon seeds, with the first ranking result being the F1 Series (3n) watermelon seeds with a preference value of 0.85442, and black box testing showed that this system was able to provide recommendations for quality watermelon seeds according to their functionality based on the application of the WP and TOPSIS methods.